The Semantics of Emotive Markers and Other Illocutionary Content. (24th May 2021) - Rett, Jessica
Abstract: I identify a class of expressions called 'emotive markers, ' exemplified by fortunately and alas, which encode not-at-issue information about the speaker's emotive attitude towards the content of the utterances they occur in. I argue that there are important differences emotive markers and other encoders of not-at-issue content, in particular utterance modifiers like frankly or evidential adverbs like apparently . In contrast to these, emotive markers can result in Moore's Paradox and always range over their local argument. I conclude that the contribution of emotive markers should be treated as 'illocutionary content', on par with the speaker's other Discourse Commitments (Gunlogson, 2001 ), and I model this analysis in the dynamic sub-sentential update framework in Farkas & Bruce (2010) .